RUMAH SEBAGAI TEMPAT BERTUMBUHNYA KARAKTER KRISTUS ; REFLEKSI PENDIDIKAN KRISTEN DALAM KELUARGA - Hendrina Lakusa; Kriatianto I. Malo; Selfi B. Manobe; Yusri K. Faot; Yayan Nopala (CV. ADIBA AISHA AMIRA, 2026)
Christian education in the family is the primary foundation for the formation of a child's faith and character. The family serves as the first environment where children learn the values ​​of the Christian faith through relationships, role models, and daily practices. However, the realities of modern life, such as busy parents, the influence of digital technology, and the weakening of role models, present serious challenges to faith education at home. This study aims to examine the role of the Christian family as a space for the formation of Christ-like character based on the theological foundations of the Bible. The study used a qualitative approach with a literature review method through analysis of the Bible, and relevant scientific articles. The results indicate that faith education in the family, carried out consciously, consistently, and relationally through parental example, plays a significant role in shaping children's character, reflecting love, obedience, humility, and self-control. Therefore, strengthening the role of parents and synergy between the family, the church, and Christian education are necessary to support the ongoing development of children's faith and character